2021
DOI: 10.34208/jba.v23i1.902
|View full text |Cite
|
Sign up to set email alerts
|

Brand Experience Untuk Memprediksi Brand Attitude Pada Konsumen Sporting Brand

Abstract: The purpose of this research is to examine whether 1a) sensory brand experience, 1b) affective brand experience, and 1c) behavioral brand experience can predict behavioral brand attitude. 2a) sensory brand experience, 2b) affective brand experience, and 2c) behavioral brand experience can predict cognitive brand attitude. 3a) sensory brand experience, 3b) affective brand experience, and 3c) behavioral brand experience can predict affective brand attitude. Sample was selected using convenience sampling method a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 11 publications
0
6
0
5
Order By: Relevance
“…This is also reinforced by research conducted by (Japutra & Keni, 2020) shows that the sensory experience dimension has a positive influence on brand attachment. Further, according (Chandra & Keni, 2021) the sensory experience dimension has a positive effect on Cognitive Experience and Affective Experience. According (Farida & Roesman, 2019) the affective experience dimension is associated with Cognitive Experience, Affective Experience and Behavioral Experience producing a positive influence.…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…This is also reinforced by research conducted by (Japutra & Keni, 2020) shows that the sensory experience dimension has a positive influence on brand attachment. Further, according (Chandra & Keni, 2021) the sensory experience dimension has a positive effect on Cognitive Experience and Affective Experience. According (Farida & Roesman, 2019) the affective experience dimension is associated with Cognitive Experience, Affective Experience and Behavioral Experience producing a positive influence.…”
Section: Introductionmentioning
confidence: 93%
“…According (Chandra & Keni, 2021) Affective experience is "which includes the feelings evoked by the brand and its emotional bond with consumers". While in (Richards, 2001) stated that "the affective dimension refers to the consumer's emotions and inner feelings towards the brand".…”
Section: Literatur Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Esta investigación investigó la lealtad de la marca y sus variables asociadas, a saber, la experiencia de marca y la participación en el producto (Chandra, 2021). El teléfono móvil se ha convertido en un componente primordial de nuestras vidas por el rápido cambio tecnológico, por lo que esta investigación permite a las empresas conocer el comportamiento de compra de los clientes (Khatab et al, 2019).…”
Section: Titleunclassified
“…Customer loyalty is also defined as use something product or service by ongoing and a psychological process that is results from commitment to product (Thakur & Gupta, 2016). (Chandra & Keni, 2021) added that consumer with level high loyalty usually will permanent use something brand though have another alternative. Then, can concluded that customer loyalty is something size faithfulness from customer in use something brand product or brand service in the period time specific to the situation where many choice product or services that can Fulfill needs and customers have ability get it.…”
Section: Customer Loyaltymentioning
confidence: 99%